Microstructure and water corrosion behavior of (Lu0.2Yb0.2Er0.2Tm0.2Sc0.2)2Si2O7 high-entropy rare-earth disilicate coating for SiC coated C/C composites. Issue 8 (July 2023) - Chen, Guohui; Zhang, Yulei; Guo, Xiaotong; Fu, Yanqin; Kong, Jing'an; Gai, Wenhan; Zhang, Pengfei
Abstract: In order to make carbon/carbon composites suitable for application in gas turbine engine, it is necessary to develop environmental barrier coatings (EBCs) to protect them from reacting with water vapor. In our previous work, a novel high-entropy rare-earth disilicate (Lu0.2 Yb0.2 Er0.2 Tm0.2 Sc0.2 )2 Si2 O7 ((5RE0.2 )2 Si2 O7 ) has been developed and verified as a promising candidate for EBCs. In this work, the (5RE0.2 )2 Si2 O7 coating was synthesized on the surface of SiC coated C/C composites by supersonic atmospheric plasma spraying method. The protective performance and mechanism of this coating under high temperature water vapor environment was explored in detail. Results showed that the weight change of the sample coated with (5RE0.2 )2 Si2 O7 was only 0.2% after corrosion for 100 h at 1500 ºC, which proved that (5RE0.2 )2 Si2 O7 coating could significantly improve the resistance of C/C composites against water vapor corrosion. This work may provide theoretical basis for the design and application of high-entropy rare-earth silicates as EBCs.